Analisis Struktur dan Vegetasi di Sempadan Sungai Ira (Wae Ira) Negeri Kamarian, Kecamatan Kairatu, Kabupaten Seram Bagian Barat - Labetubun, Agung Herat; Irwanto, Irwanto; Tetelay, Febian Filiph (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the structure and composition of vegetation on the banks of the Ira River (Wae Ira), Negeri Kamarian, Kairatu District, West Seram Regency. Riparian vegetation plays an important role in maintaining the stability of river ecosystems, both in terms of ecological, hydrological, and biodiversity aspects. The method used in this study is a combination of the continuous strip sampling method and the line plot sampling method, which are applied to four levels of vegetation growth, namely seedlings, saplings, poles, and trees. The results of the analysis show that the vegetation structure in the study area is divided into four strata, with varying species compositions in each stratum. The dominant species found include Pulai (Alstonia scholaris), Pulaka (Cyrtosperma merkusii), Buah rao (Dracontomelon mangiferum), and Salam (Syzygium polyanthum). The highest Importance Value Index (INP) at the tree level is owned by Pulai (Alstonia scholaris) at 54,2. The highest vegetation density is at the seedling level with 52000 individuals/ha and the lowest at the tree level with 341 individuals/ha. The Shannon-Wiener diversity index (H') ranges from 1.87–2.65, indicating a moderate level of diversity. The results of this study indicate that the Ira River border area still has a relatively good vegetation structure and composition, although there are ecological pressures that cause dominance by certain species